Whole Genome Sequencing of Drug Resistant and Drug Susceptible Mycobacterium tuberculosis Isolates From Tigray Region, Ethiopia - Welekidan, Letemichael Negash; Yimer, Solomon Abebe; Skjerve, Eystein; Dejene, Tsehaye Asmelash; Homberset, Håvard; Tønjum, Tone; Brynildsrud, Ola (Frontiers in Microbiology, 2021)
Background Tuberculosis, mainly caused by Mycobacterium tuberculosis (Mtb)), is an ancient human disease that gravely affects millions of people annually. We wanted to explore the genetic diversity and lineage-specific association of Mtb with drug resistance among pulmonary tuberculosis patients. Methods Sputum samples were collected from pulmonary tuberculosis patients at six different healthcare institutions in Tigray, Ethiopia, between July 2018 to August 2019. DNA was extracted from 74 Mtb complex isolates for whole-genome sequencing (WGS). All genomes were typed and screened for mutations with known associations with antimicrobial resistance using in silico methods like the program colltyper, microbe predictor, TB-profiler, Snippy-core, auspice.us, and results were cross-verified with wet lab methods. Results Lineage (L) 4 (55·8%) was predominant, followed by L3 (41·2%); L1 (1·5%) and L2 (1·5%) occurred rarely. The most frequently detected sublineage was CAS (38·2%), followed by Ural (29·4%), and Haarlem (11·8%). The recent transmission index (RTI) was very high. L4 and Ural strains were more resistant than the other strains to any anti-TB drug (P <0·05). The most frequent mutations to RIF, INH, ETB, SM, PZA, ETH, FLQs, and 2nd-line injectable drugs occurred at rpoB S450L, katG S315T, embB M306I/V, rpsL K43R, pncA V139A, ethA M1R, gyrA D94G, and rrs A1401G, respectively. Disputed rpoB mutations were also shown in four (16%) of RIF-resistant isolates. Conclusion Our WGS analysis revealed the presence of diverse Mtb genotypes. The high level of RTI and the presence of a significant proportion of disputed rpoB mutations highlighted the need to establish a WGS facility at the regional level to monitor drug-resistant mutations. This will help control the transmission of DR-TB and ultimately contribute to the attainment of 100% DST coverage for TB patients as per the End TB strategy.